Books on Spirituality - Conn, Joann Wolski (Theology today, 1982)
Mysterion: An Approach to Mystical Spirituality, by Richard Woods (Chicago, Thomas More, 1981. 371 pp. $14.95); True Prayer: An Invitation to Christian Spirituality, by Kenneth Leech (San Francisco, Harper & Row, 1980. 202 pp. $10.95); The Call of Silence: Discovering Christian Meditation, by Bradley Hanson (Minneapolis, Augsburg, 1980. 140 pp. $5.95, paper); Prayer of the Heart, by George A. Maloney, S.J. (Notre Dame, Ave Maria, 1981. 206 pp. $3.95 paper).